Palladium-catalyzed regioselective olefination of O-acetyl cyanohydrins - Liang, Qiu-Ju (2020)
A practical palladium-catalyzed ortho-olefination of O-acetyl cyanohydrins assisted by synergetic directing groups has been developed. Thus, a range of olefinated O-acetyl cyanohydrins were synthesized in moderate to good yields. The reaction occurs efficiently with high regioselectivity and with a satisfactory tolerance of functional groups.